EFEKTIVITAS HEALTH EDUCATION DAN TERAPI RELAKSASI TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - Khodijah, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Hypertension is a condition where systolic blood pressure is higher than 140 mmHg and diastolic is higher than 90 mmHg. Objective: to determine the effectiveness of health education and relaxation therapy on blood pressure in hypertensive patients. Methods: The sources of the articles used were obtained from searches through the databases of Google Scholar, Pubmed, and Google Cindekia. Article search is restricted from 2017-2022. After the article is obtained, then the article is reviewed until the stage of making a literature review. The keywords used in the search were Health education on blood pressure in hypertensive patients and Effect of relaxation therapy on blood pressure in hypertensive patients. This literature review uses 15 articles that meet the inclusion criteria. Results: there is an effective effect of health education and relaxation therapy on blood pressure in hypertensive patients. Conclusion: educational interventions and relaxation therapy have a positive impact on lifestyle and reduce blood pressure in hypertensive patients and prevent complications